Biocatalytic benefits of immobilized Fusarium sp. (GFC) lipase from solid state fermentation on free lipase from submerged fermentation - de Oliveira, Bruno Henrique [UNESP]; Coradi, Gilberto Victor [UNESP]; de Oliva-Neto, Pedro [UNESP]; do Nascimento, Valeria Marta Gomes [UNESP] (Elsevier, 2020)
Lipases are promising tools for the synthesis of high value-added compounds and have traditionally been obtained from submerged fermentation processes (SmF). However, solid-state fermentation (SSF) allows linking the fermentation process directly to the enzyme application. Using fermented substrate as the biocatalysts may combine the steps of enzyme production, extraction, purification and immobilization together. There are also other advantages in SSF as a cheaper growing medium like crambe (Crambe hispanica subsp. abyssinica Hochst. ex R.E.Fr. - Brassicaceae). This study explores the use of crambe cake fermented with Fusarium sp. (GFC) as a source of lipase in a comparison with the enzyme traditionally produced by SmF and its directly aplication in hydrolisys and synthesys reations. Besides being produced at low fermentation cost, the SSF enzyme was obtained as a naturally immobilized lipase and presented activity and stability at medium temperatures (40 and 45 °C) and a good stability towards organic solvents. Using the potential of those characteristics, the fermented substrate enzyme was successfully applied to an optimization of methyl ester synthesis in organic media with up to 8 viable recycles. Therefore, all results support the search for potential applications of the Fusarium sp. (GFC) enzyme in biocatalysis, since its characteristics and low production cost.
Keywords: Crambe abyssinica; Ethyl oleate synthesis; Factorial design; Gibberella fujikuroicomplex; Methyl oleate synthesis; Triacylglycerol acylhydrolases